Ackerman's surgical pathology - Rosai, Juan; Ackerman, Lauren Vedder, 1905- (St. Louis : Mosby, 1998)
This CD-ROM allows you to easily and quickly navigate through more than 2,700 pages and 3,300 high-quality illustrations.
System requirements: Windows; 486 or Pentium-based PC, running Windows 95, Windows NT, or Windows 3.1 (Windows 3.1 requires installed TCP/IP stack and configured modem), 16 MB RAM minimum and 20 MB free hard disk space, 2Xor faster CD-ROM drive, 640 x 480 monitor with thousands of colors or better, 28.8 or faster modem (optional for internet access)
System requirements: Macintosh; For the Macintosh and Power PC systems running System 7.5 or newer: 16 MB RAM minimum and 20 MB free hard disk space, 2X or faster CD-ROM drive, 640 x 480 monitor with thousands of colors or better, 28.8 or faster modem (optional for internet access)
Keywords: Pathology, Surgical